2015
DOI: 10.1088/0004-6256/150/2/62
|View full text |Cite
|
Sign up to set email alerts
|

A Search for Substellar Companions to the Two Nearest Brown Dwarf Systems

Abstract: WISE J104915.57−531906.1 A+B and WISE J085510.83−071442.5 were recently discovered as the third and fourth closest known systems to the Sun, respectively (2.0 and 2.3 pc). The former consists of a L8+T0.5 binary and the latter is a probable Y dwarf and is the coldest known brown dwarf (∼ 250 K). We present a search for common proper motion companions to these brown dwarfs using multi-epoch mid-infrared images from the Spitzer Space Telescope. We have also obtained near-infrared adaptive optics images of WISE J… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…(i) We rule out co-moving companions down to Y dwarf spectral types in the range 1-80 AU. This result confirms the finding of Melso et al (2015), which is based on superior data for this analysis. Note that Melso et al also extended this investigation at wider separations.…”
Section: Discussionsupporting
confidence: 91%
“…(i) We rule out co-moving companions down to Y dwarf spectral types in the range 1-80 AU. This result confirms the finding of Melso et al (2015), which is based on superior data for this analysis. Note that Melso et al also extended this investigation at wider separations.…”
Section: Discussionsupporting
confidence: 91%
“…We have also included all previous Spitzer observations of the object (Luhman 2014;Melso et al 2015) and two photometric monitoring campaigns with Spitzer that will be presented by T. Esplin (2016, in preparation).…”
Section: Observationsmentioning
confidence: 99%
“…The second of those observations consisted of a large map (840″×840″) rather than a single field of view of the camera. Melso et al (2015) performed a second map of the same size in 2015, corresponding to the fifth epoch overall. We have measured astrometry for WISE 0855-0714 from all epochs of [4.5] images except the two photometric monitoring campaigns.…”
Section: Spitzer Irac Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, the first directly imaged exoplanet orbits a BD (Chauvin et al 2004(Chauvin et al , 2005 and the nearest planet was discovered with radial velocity monitoring of the M-type star (Anglada-Escudé et al 2016). Hubble Space Telescope (HST) imaging found no companions of W0855 within 0.5 AU Zapatero Osorio et al 2016) and Spitzer imaging reported none within 9-970 AU (Melso et al 2015). Unfortunately, the object is too faint for radial velocity monitoring even with the best current or near-future spectrographs.…”
Section: Introductionmentioning
confidence: 99%